2014
DOI: 10.2298/tsci130131086g
|View full text |Cite
|
Sign up to set email alerts
|

Emission characteristics of iso-propanol/gasoline blends in a spark-ignition engine combined with exhaust gas re-circulation

Abstract: Experiments were carried out in a spark-ignition engine fueled with iso--propanol/gasoline blends. Emission characteristics of this engine were investigated experimentally, including gaseous emissions (HC, CO, NO x ) and particulate matter emission in term of number and size distributions. The effects of different iso-propanol percentages, loads and exhaust gas re-circulation rates on emissions were analyzed. Results show that the introduction of exhaust gas re-circulation reduces the NO x emission and NO x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…14,15 Isopropanol has, however, been studied previously in both spark ignition and HCCI engines to examine its potential as a gasoline additive. [16][17][18][19][20][21] Results of these studies show significantly reduced CO and HC emissions, 16 and virtually zero NO emissions in HCCI engines, being noted as more suitable for HCCI combustion in its knock prevention. 20 Isopropanol has also been studied in diffusion flames 22,23 and more recently in both premixed and nonpremixed flames using more advanced speciation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Isopropanol has, however, been studied previously in both spark ignition and HCCI engines to examine its potential as a gasoline additive. [16][17][18][19][20][21] Results of these studies show significantly reduced CO and HC emissions, 16 and virtually zero NO emissions in HCCI engines, being noted as more suitable for HCCI combustion in its knock prevention. 20 Isopropanol has also been studied in diffusion flames 22,23 and more recently in both premixed and nonpremixed flames using more advanced speciation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, some works that study the benefits of combining fuel blends with the EGR can be found. The experiments carried out by J. Gong et al [15] on an SI engine fueled with various iso-propanol/gasoline blends showed an increased in the PN emissions when the volume fraction of iso-propanol in the blend increased. However, the concentration of the particles decreased considerably with the increased of the EGR rate, in conditions of mixture rich in iso-propanol, making viable the use of iso-propanol and its benefits, among which are the decrease in NOx emissions.…”
Section: Introductionmentioning
confidence: 99%
“…C 1 –C 5 alcohols can be used in small fractions in both spark ignition (SI) and compression ignition (CI) engines without major modifications. Alcohol blends are used frequently in SI engines, whereas in CI engines, blends, emulsions, fumigation, or multiple injections are used. Methanol, ethanol, and various isomers of butanol have been extensively studied. ,, Investigation on propanol is rare and mainly limited to homogenous charge compression ignition (HCCI) combustion. , As a result of its physical and chemical properties, n -pentanol is mainly used as an additive to diesel or biodiesel.…”
Section: Introductionmentioning
confidence: 99%